If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+10)=(4x-40)
We simplify the equation to the form, which is simple to understand
(3x+10)=(4x-40)
Remove unnecessary parentheses
3x+10=(4x-40)
Remove unnecessary parentheses
3x+10=4x-40
We move all terms containing x to the left and all other terms to the right.
+3x-4x=-40-10
We simplify left and right side of the equation.
-1x=-50
We divide both sides of the equation by -1 to get x.
x=50
| 3b-5-5b-3= | | 2x+3=x+5+x | | 15=5x+60 | | X*15=12 | | 46=n-13 | | -12y-3=-11y+8 | | (x+7)(x-3)=11 | | (10x-18)=(8x+14) | | 26+0.15p=c | | 6(W-3)=6W-18 | | 16-5*3= | | 8x-15=4x-(-12) | | 6=3(m+5)+3(m+3) | | 64x^3-81x=0 | | 10=x-15 | | 0.2p=9 | | 10=5(x-2)+5x | | s=0.1666666667w | | (68-x)=3x | | 100x^3-121x=0 | | 94=7x+17 | | 3.5=1.6-0.4y | | 5X-4=8x+11 | | 4x^2+7xy+3y^2= | | 9-5a=8a-17 | | x-3x=40 | | 5n+10n+25n=340 | | -21-8x=-5(x+6) | | x=-2y+10 | | 3(2x-5)=(3x-2) | | 3(2x-5)=3x-2 | | -42x-12=42x+7+12 |